Searching for 0νββ Decay in 136Xe: Toward the Ton-Scale and Beyond. (3rd July 2017) - Brunner, T.; Winslow, L.
Abstract : The quest for neutrinoless double-beta decay (0νββ) is a promising experimental approach to search for lepton number violation in weak interactions, a key ingredient in generating the matter-antimatter asymmetry through models of Leptogenesis. The 136 Xe-based 0νββ experiments KamLAND-Zen and EXO-200 currently set the most stringent limits on this process using two very different techniques. Each are preparing the next generation experiment, which will search for 0νββ in the parameter space corresponding to the inverted hierarchy for neutrino mass. Both of these techniques scale well to larger volumes while incorporating interesting new techniques. We present the status of current and next generation experiments of these collaborations and present two developments with the potential to identify ββ decay events.